2023
DOI: 10.3390/ijms24119430
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Tail of Mitochondrial Transcription Factor A Is Dispensable for Mitochondrial DNA Replication and Transcription In Situ

Abstract: Mitochondrial transcription factor A (TFAM) is one of the widely studied but still incompletely understood mitochondrial protein, which plays a crucial role in the maintenance and transcription of mitochondrial DNA (mtDNA). The available experimental evidence is often contradictory in assigning the same function to various TFAM domains, partly owing to the limitations of those experimental systems. Recently, we developed the GeneSwap approach, which enables in situ reverse genetic analysis of mtDNA replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Recently, it has been demonstrated that the TFAM tail is dispensable for mtDNA replication and transcription in situ. This evidence represents a challenge to the current model of mtDNA transcription, which postulates a critical role for the TFAM tail in the assembly of the mitochondrial transcription apparatus [ 43 ].…”
Section: Functional Roles Of Tfam Domainsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, it has been demonstrated that the TFAM tail is dispensable for mtDNA replication and transcription in situ. This evidence represents a challenge to the current model of mtDNA transcription, which postulates a critical role for the TFAM tail in the assembly of the mitochondrial transcription apparatus [ 43 ].…”
Section: Functional Roles Of Tfam Domainsmentioning
confidence: 99%
“…However, recent evidence from the higher-order structures of the transcriptional apparatus indicates that TFAM binds in the same orientation at the LSP and HSP1 [ 42 ]. Therefore, it is unclear why TFAM bending mutants have a greater effect on LSP transcription than on HSP1 transcription in vitro [ 36 , 50 ], or why the effects of bending mutations on mitochondrial promoters are reversed in situ [ 43 ].…”
Section: Tfam Dna Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, LSP transcription appears to depend on TFAM, particularly on its C-terminus [ 7 ]. However, more recent evidence has suggested that tail-less TFAM can initiate LSP transcription on longer DNA templates [ 8 , 9 ] and can support mtDNA transcription and replication in situ [ 10 ]. Notably, the initiation of the lagging mtDNA strand replication appears to be TFAM-independent [ 11 , 12 ].…”
mentioning
confidence: 99%